Analisis Perbedaan Komponen Pidana Sistem Hukum Civil Law dan Common Law - Habsy Ahmad; Chairul Amri (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
This study aims to find out what are the criminal components contained in the civil law and common law legal systems and to find out the differences between the criminal components of the civil law and common law legal systems. In this study, the authors use a type of normative legal research, namely legal research that views law as a social phenomenon. The population in this study are objects of continental European law (civil law) and objects of Anglo-Saxon law (common law) whose sources are both legal science (literature) and the differences in the criminal components of the two legal systems in question. The results of this study indicate that the civil law legal system prioritizes legislation as its main pillar, in this system more laws are formed through statutory regulations. The sources of law in the Civil Law System appear to play a very important role in human-made laws or what are later referred to as statutes or written laws. Countries with a Romano-Germanic system are also called countries with a written legal system.